2014
DOI: 10.1002/hup.2427
|View full text |Cite
|
Sign up to set email alerts
|

The effect of desvenlafaxine 50 mg/day on a subpopulation of anxious/depressed patients: a pooled analysis of seven randomized, placebo‐controlled studies

Abstract: Desvenlafaxine 50 mg/day significantly improved depressive symptoms compared with placebo in major depressive disorder patients with clinically relevant anxiety symptoms. Improvement in the HAM-D17 total score was similar for anxious/nonanxious groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Duloxetine had significantly greater efficacy for treating depression compared with placebo in both anxious and nonanxious patients, based on response, remission, and depression scale scores (Nelson, 2010). Desvenlafaxine treatment was associated with significantly greater improvement from baseline in HAM-D 17 total score, and significantly higher rates of HAM-D response and remission compared with placebo in low and high anxiety groups (Kornstein et al , 2014), although it has never formally been studied or approved for any anxiety indication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duloxetine had significantly greater efficacy for treating depression compared with placebo in both anxious and nonanxious patients, based on response, remission, and depression scale scores (Nelson, 2010). Desvenlafaxine treatment was associated with significantly greater improvement from baseline in HAM-D 17 total score, and significantly higher rates of HAM-D response and remission compared with placebo in low and high anxiety groups (Kornstein et al , 2014), although it has never formally been studied or approved for any anxiety indication.…”
Section: Discussionmentioning
confidence: 99%
“…Although antidepressant medications have generally similar efficacy within and between classes when used to treat depression (Gelenberg et al , 2010), and a range of antidepressant drugs have been shown to be effective in treating depression with anxiety (Tollefson et al , 1994; Bandelow et al , 2007; Nelson, 2010; Kornstein et al , 2014; Stein et al , 2013), several studies suggest that there may be efficacy differences among drugs in MDD patients with symptoms of anxiety. For example, in analyses of depressed patients with high levels of anxiety symptoms at baseline, patients treated with selective serotonin reuptake inhibitors (SSRIs) had greater response rates than in those treated with bupropion (Papakostas et al , 2008), and patients treated with the serotonin–norepinephrine reuptake inhibitor (SNRI) venlafaxine (extended release or immediate release) had significantly greater rates of remission compared with patients treated with fluoxetine (Davidson et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Venlafaxine, however, was the only antidepressant that demonstrated a specific anxiolytic effect in the postpartum depressed population [Cohen et al 2001]. Since anxiety symptoms almost invariably accompany postpartum depression [Kornstein et al 2014a; Tourian et al 2010a], careful antidepressant selectivity is crucial in managing comorbid anxiety and depressive symptoms [Misri et al 2015]. Desvenlafaxine, a metabolite of venlafaxine, appears to be an effective first-line antidepressant for the treatment of major depressive disorder (MDD) [Lam et al 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Desvenlafaxine, a metabolite of venlafaxine, appears to be an effective first-line antidepressant for the treatment of major depressive disorder (MDD) [Lam et al 2009]. It has also been shown to have anxiolytic properties [Kornstein et al 2014a; Tourian et al 2010a] and an easy dosing profile with minimal to no titration [Kornstein et al 2014b; Pfizer Canada Inc., 2014]. The tolerability profile of desvenlafaxine demonstrates that the adverse effects of weight gain and sexual dysfunction are minimal [Kornstein et al 2014b; Clayton et al 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Desvenlafaxine has a favorable safety and tolerability profile in adults with MDD, with low rates of side effects common to antidepressants, such as sexual dysfunction and weight gain . It has established efficacy over placebo at the approved doses of 50 mg/d and 100 mg/d in multiple clinical trials, and its efficacy has been demonstrated across age and sex subgroups and in patients with metabolic syndrome or anxious or severe depression at baseline in pooled post hoc analyses . Treatment with desvenlafaxine has also been shown to improve functional outcomes and quality‐of‐life measures compared with placebo in clinical trial patients …”
mentioning
confidence: 99%